Influencing factors of willingness to promote human papillomavirus vaccination in Chinese male university students - Zhen-wei DAI; Ming-yu SI; Wen-jun WANG; Xiao-you SU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo describe the awareness of human papillomavirus (HPV) among male university students in China, and to explore potential influencing factors of the students' intention to encourage others to have HPV vaccination. Methods Using convenient sampling and a self-designed questionnaire on demographics, health and sexual behavior, and knowledge and attitude about HPV, we conducted an online voluntary survey among 3 570 male undergraduates of 7 universities in 7 provincial-level administrative divisions across China during February 21 - April 30, 2021. ResultsOf all the participants, 3 213 reported the willingness of promoting HPV vaccination in their friends. The results of logistic regression analysis showed that the students with following characteristics were more likely to promote HPV vaccination in their friends: agreeing with that HPV vaccination could prevent some diseases effectively (odds ratio [OR] = 2.011, P＜0.001), ever receiving a self-paid category II vaccine (OR = 1.652, P＜0.001), ever participating in education programs about sexual health (OR = 1.619, P＜0.001), with positive attitude towards premarital sex (OR = 1.366，P = 0.012), having high knowledge about HPV (OR = 1.498，P = 0.002), and with a perceived benefit of HPV vaccination (OR = 3.225，P＜0.005). ConclusionThe survey results suggest that relative departments could conduct interventions on the awareness and attitude about HPV vaccination among male university students to promote HPV vaccination in China.